AN ANALYSIS OF THE ENGLISH NEEDS OF FIFTH GRADERS AS PERCEIVED BY THE TEACHERS IN SEVERAL SCHOOLS IN ONE OF THE SUBDISTRICTS IN CIREBON - Ghea Kyat Priyanka, - (2018)
Tesis ini dilatarbelakangi oleh fakta yang mengungkapkan bahwa mayoritas sekolah dasar di Cirebon menerapkan Bahasa Inggris sebagai muatan lokal meskipun para guru merasa kebingungan akan pengembangan materi karena kurangnya panduan dalam mempersiapkan materi Bahasa Inggris di kurikulum sekolah dasar. Oleh karena itu, tesis ini bertujuan untuk mengidentifikasi kebutuhan siswa dalam mempelajari Bahasa Inggris sebagai bahasa asing melalui perspektif guru sekolah dasar dan guru sekolah menengah pertama demi menunjang proses persiapan materi Bahasa Inggris bagi siswa sekolah dasar. Pendekatan kualitatif dengan menggunakan kuesioner, wawancara, dan observasi dilaksanakan pada 17 guru sekolah dasar dan 5 guru sekolah menengah pertama. Hasil penelitian mununjukkan bahwa guru sekolah dasar maupun guru sekolah menengah pertama mengakui bahwa kemampuan rata-rata siswa mereka tergolong rendah karena minimnya pengetahuan kosakata dan tata bahasa dalam Bahasa Inggris. Akar masalah dari pengembangan kemampuan siswa berasal dari penguasaan kosakata. Hal ini memengaruhi tingkat percaya diri dan juga ketergantungan siswa akan bantuan guru dalam proses belajar. Oleh karena itu, guru sekolah dasar disarankan untuk menekankan proses pembelajaran pada penguasaan kosakata demi meningkatnya kemampuan siswa dalam pembelajaran Bahasa Inggris. This study was motivated by the fact revealing that majority of the elementary schools in Cirebon implemented English as their elective local content subject despite teachers' confusion towards material development due to lack of guidance in preparing English materials in elementary school curriculum. Therefore, this study is aimed at identifying elementary students' needs in learning English as a Foreign Language as perceived by elementary and junior high school teachers in order to support the process of material preparation for elementary students. Questionnaire, semi-standardized interview, and observation under qualitative study were administered to 17 elementary school teachers and 5 junior high school teachers. The findings came up that both elementary and junior high school teachers considered their students' overall skills low due to their poor vocabulary and grammatical knowledge. It was revealed that any issues found in the study rooted in students' vocabulary mastery. This concerned issue affected students' self confidence and dependency in English learning. For that reason, elementary school teachers are suggested to put emphasis on vocabulary teaching in order to promote students' improvement in English learning. This study was motivated by the fact revealing that majority of the elementary schools in Cirebon implemented English as their elective local content subject despite teachers' confusion towards material development due to lack of guidance in preparing English materials in elementary school curriculum. Therefore, this study is aimed at identifying elementary students' needs in learning English as a Foreign Language as perceived by elementary and junior high school teachers in order to support the process of material preparation for elementary students. Questionnaire, semi-standardized interview, and observation under qualitative study were administered to 17 elementary school teachers and 5 junior high school teachers. The findings came up that both elementary and junior high school teachers considered their students' overall skills low due to their poor vocabulary and grammatical knowledge. It was revealed that any issues found in the study rooted in students' vocabulary mastery. This concerned issue affected students' self confidence and dependency in English learning. For that reason, elementary school teachers are suggested to put emphasis on vocabulary teaching in order to promote students' improvement in English learning.